Immuno-PET Imaging of the Programmed Cell Death-1 Ligand (PD-L1) Using a Zirconium-89 Labeled Therapeutic Antibody, Avelumab - Elaine M. Jagoda PhD; Olga Vasalatiy PhD; Falguni Basuli PhD; Ana Christina L. Opina PhD; Mark R. Williams BS; Karen Wong MS; Kelly C. Lane BS; Steve Adler PhD; Anita Thein Ton MS; Lawrence P. Szajek PhD; Biying Xu PhD; Donna Butcher BS; et al. (Molecular Imaging)
Objective: The goal is to evaluate avelumab, an anti-PD-L1 monoclonal immunoglobulin G antibody labeled with zirconium-89 in human PD-L1-expressing cancer cells and mouse xenografts for clinical translation. Methods: [ 89 Zr]Zr-DFO-PD-L1 monoclonal antibody (mAb) was synthesized using avelumab conjugated to desferrioxamine. In vitro binding studies and biodistribution studies were performed with PD-L1+MDA-MB231 cells and MDA-MB231 xenograft mouse models, respectively. Biodistributions were determined at 1, 2, 3, 5, and 7 days post coinjection of [ 89 Zr]Zr-DFO-PD-L1 mAb without or with unlabeled avelumab (10, 20, 40, and 400 µg). Results: [ 89 Zr]Zr-DFO-PD-L1 mAb exhibited high affinity (K d ∼ 0.3 nM) and detected moderate PD-L1 expression levels in MDA-MB231 cells. The spleen and lymph nodes exhibited the highest [ 89 Zr]Zr-DFO-PD-L1 mAb uptakes in all time points, while MDA-MB231 tumor uptakes were lower but highly retained. In the unlabeled avelumab dose escalation studies, spleen tissue–muscle ratios decreased in a dose-dependent manner indicating specific [ 89 Zr]Zr-DFO-PD-L1 mAb binding to PD-L1. In contrast, lymph node and tumor tissue–muscle ratios increased 4- to 5-fold at 20 and 40 µg avelumab doses. Conclusions: [ 89 Zr]Zr-DFO-PD-L1 mAb exhibited specific and high affinity for PD-L1 in vitro and had target tissue uptakes correlating with PD-L1 expression levels in vivo. [ 89 Zr]Zr-DFO-PD-L1 mAb uptake in PD-L1+tumors increased with escalating doses of avelumab.